2014
DOI: 10.4321/s1886-36552014000100007
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a pharmacist: the role of curriculum in professional identity formation

Abstract: ObjectiveTo understand how the formal curriculum experience of an Australian undergraduate pharmacy program supports students’ professional identity formation.MethodsA qualitative ethnographic study was conducted over four weeks using participant observation and examined the ‘typical’ student experience from the perspective of a pharmacist. A one-week period of observation was undertaken with each of the four year groups (that is, for years one to four) comprising the undergraduate curriculum. Data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 46 publications
0
52
0
Order By: Relevance
“…“Good tools can be used badly.” (p36) Unfortunately regardless of how well a competence framework is written, it is useless if not sustainably embedded or effectively supported . Australian pharmacists' disengagement with their NCS could be a symptom of inconsistent use of competence terminology, self‐regulated accreditation practices, inadequate use of mentor models for early career pharmacists and peer review of practice, poor applicability and usability of NCS in pharmacy education, issues with professional identity formation, and an accountability ‘tick and flick’ audit mentality to maintaining competence rather than a responsible commitment to life‐long learning. Our survey respondents suggested meaningful use of the NCS for life‐long learning could improve through focus on early intervention with students, periodic refreshers on self‐assessment skills training as well as NCS awareness in the future.…”
Section: Discussionmentioning
confidence: 99%
“…“Good tools can be used badly.” (p36) Unfortunately regardless of how well a competence framework is written, it is useless if not sustainably embedded or effectively supported . Australian pharmacists' disengagement with their NCS could be a symptom of inconsistent use of competence terminology, self‐regulated accreditation practices, inadequate use of mentor models for early career pharmacists and peer review of practice, poor applicability and usability of NCS in pharmacy education, issues with professional identity formation, and an accountability ‘tick and flick’ audit mentality to maintaining competence rather than a responsible commitment to life‐long learning. Our survey respondents suggested meaningful use of the NCS for life‐long learning could improve through focus on early intervention with students, periodic refreshers on self‐assessment skills training as well as NCS awareness in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In PS, learning comprises (i) content (experimenting), (ii) practice (practicing), (iii) workplace environment and culture (feeling of belonging), and (iv) development of professional identity (transformation). 19,22 Hence, while preparing the pharmacy curriculum, the question to be prioritized should be "at what rate do the curricula enable practices and experiences that will help students feel themselves as 'pharmacists'? ", rather than "do we prepare curricula that cover all the knowledge that students need to acquire?".…”
Section: Different Approaches In Pharmacy Educationmentioning
confidence: 99%
“…24 This disparity causes students to feel disappointed and have difficulty in performing their role as a provider. 14, 22 As a result, students can neither benefit from pharmacy education nor pursue their profession with full job satisfaction.…”
Section: Current State Of Pharmaceutical Services In Turkeymentioning
confidence: 99%
See 1 more Smart Citation
“…5 Noble and colleagues observed that development of professional identity in student pharmacists is difficult due in part to the broad range of pharmacists' roles. 7 They used an ethnographic approach to study the culture of a pharmacy program, with one author making field observations while embedded in courses over the period of a month and interacting with students as they went through their normal program-based activities, including classes and labs. One of their findings was that many clinical faculty were seen by students as educators rather than as pharmacists, so the opportunity to develop their own professional identity from interactions with these clinical faculty was minimized.…”
Section: Introductionmentioning
confidence: 99%